A chemically stable peptide agonist to neuromedin U receptor type 2. Issue 10 (15th May 2020) - Takayama, Kentaro; Mori, Kenji; Tanaka, Akiko; Sasaki, Yu; Sohma, Yuko; Taguchi, Akihiro; Taniguchi, Atsuhiko; Sakane, Toshiyasu; Yamamoto, Akira; Miyazato, Mikiya; Minamino, Naoto; Kangawa, Kenji; et al.
Graphical abstract: Abstract: Neuromedin U (NMU) is a peptide with appetite suppressive activity and other physiological activities via activation of the NMU receptors NMUR1 and NMUR2. In 2014, we reported the first NMUR2 selective agonist, 3-cyclohexylpropionyl-Leu-Leu-Dap-Pro-Arg-Asn-NH2 (CPN-116). However, we found that CPN-116 in phosphate buffer is unstable because of N α -to- N β acyl migration at the Dap residue. In this study, the chemical stability of CPN-116 was evaluated under various conditions, and it was found to be relatively stable in buffers such as HEPES and MES. We also performed a structure-activity relationship study to obtain an NMUR2-selective agonist with improved chemical stability. Consequently, CPN-219 bearing a Dab residue in place of Dap emerged as a next-generation hexapeptidic NMUR2 agonist.